Hesperetin-5,7,3ʹ-O-Trimethylether Dually Inhibits Phosphodiesterase 3/4 and Methacholine-Induced Airway Hyperresponsiveness in Sensitized and Challenged Mice - Shih CH; Wang WH; Chen CM; Ko WC (Dove Medical Press, 2020)
Chung-Hung Shih,1,2 Wen-Hung Wang,3 Chi-Ming Chen,4 Wun-Chang Ko3 1Division of Thoracic Medicine, Department of Internal Medicine, Taipei Medical University Hospital, Taipei 110, Taiwan; 2School of Respiratory Therapy, College of Medicine, Taipei Medical University, Taipei 110, Taiwan; 3Department of Pharmacology, School of Medicine, College of Medicine, Taipei Medical University, Taipei 110, Taiwan; 4Department of Medicinal Chemistry, School of Pharmacy, College of Pharmacy, Taipei Medical University, Taipei 110, TaiwanCorrespondence: Wun-Chang KoDepartment of Pharmacology, School of Medicine, College of Medicine, Taipei Medical University, 250 Wu-Hsing St., Taipei 110, TaiwanTel +886-2-2736-1661 Ext 3035Fax +886-2-2722-0497Email wc_ko@tmu.edu.twIntroduction: Hesperetin-5,7,3ʹ-O-trimethylether (HTME), a synthetic liposoluble hesperetin, has been reported to be a dual phosphodiesterase (PDE)3/4 inhibitor. We investigated its inhibitory effects on methacholine (MCh)-induced airway hyperresponsiveness (AHR) and its potential for treating atypical asthma and COPD.Methods: FlexiVent system was used to determine AHR in ovalbumin (OVA) sensitized and challenged mice. Determination of cytokines was performed by using mouse T helper (Th)1/Th2 cytokine CBA kits, and of total immunoglobulin (Ig)E and OVA-specific IgE using ELISA kits. The number of inflammatory cells was counted using a hemocytometer. Xylazine/ketamine-induced anesthesia was to assess nausea, vomiting, and gastric hypersecretion in these mice.Results: HTME dually and competitively inhibited PDE3/4 activities in the Lineweaver–Burk analysis. HTME (30 and 100 μmol/kg) dose-dependently and significantly decreased the airway resistance (RL) and increased lung dynamic compliance (Cdyn) values induced by MCh. It significantly suppressed numbers of total inflammatory cells and neutrophils, and levels of cytokines in bronchoalveolar lavage fluid (BALF). HTME dose-dependently and significantly inhibited total and OVA-specific IgE levels in the BALF and serum. However, HTME did not influence xylazine/ketamine-induced anesthesia.Conclusion: HTME exerted anti-inflammatory and bronchodilator effects and may be useful in treating chronic obstructive pulmonary disease and allergic atypical asthma with no gastrointestinal side effects.Keywords: allergic asthma, chronic obstructive pulmonary disease, therapeutic PDE4H/PDE4L ratio, ovalbumin, cytokines, bronchoalveolar lavage fluid, inflammation